2017
DOI: 10.1371/journal.pntd.0006010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Zika virus induced small RNA response in Aedes aegypti cells

Abstract: RNA interference (RNAi) controls arbovirus infections in mosquitoes. Two different RNAi pathways are involved in antiviral responses: the PIWI-interacting RNA (piRNA) and exogenous short interfering RNA (exo-siRNA) pathways, which are characterized by the production of virus-derived small RNAs of 25–29 and 21 nucleotides, respectively. The exo-siRNA pathway is considered to be the key mosquito antiviral response mechanism. In Aedes aegypti-derived cells, Zika virus (ZIKV)-specific siRNAs were produced and load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
139
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(158 citation statements)
references
References 55 publications
(81 reference statements)
18
139
1
Order By: Relevance
“…In many species, including insects, RNA interference (RNAi) serves as a system of adaptive antiviral immunity. The importance of RNAi-mediated immunity and viral evasion strategies is exemplified by insects that transmit a wide variety of viral infectious agents to humans including sandfly fever, Dengue, Chikungunya, and Zika virus (Blair, 2011; Nayak et al, 2013; Varjak et al, 2017). The insect antiviral RNAi response requires the Dicer-2 (Dcr2) and the Argonaute 2 (Ago-2) enzymes, which cleaves double-stranded (ds) viral RNA replication intermediates and single-stranded viral RNA genomes, respectively, to limit virus replication (Aliyari et al, 2008; Marques et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In many species, including insects, RNA interference (RNAi) serves as a system of adaptive antiviral immunity. The importance of RNAi-mediated immunity and viral evasion strategies is exemplified by insects that transmit a wide variety of viral infectious agents to humans including sandfly fever, Dengue, Chikungunya, and Zika virus (Blair, 2011; Nayak et al, 2013; Varjak et al, 2017). The insect antiviral RNAi response requires the Dicer-2 (Dcr2) and the Argonaute 2 (Ago-2) enzymes, which cleaves double-stranded (ds) viral RNA replication intermediates and single-stranded viral RNA genomes, respectively, to limit virus replication (Aliyari et al, 2008; Marques et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The RNA interference pathway (RNAi) is a major antiviral defense initiated by the recognition of viral replication intermediates by the Dicer-2 protein [46]. This pathway inhibits the replication of DENV and ZIKV viruses in the midgut and salivary glands of mosquitoes [4749]. Interestingly, Myles and colleagues recently showed that the YFV C protein counteracts the RNA interference pathway in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…aegypti cell line Aag2 using arboviruses. Gene silencing of Piwi5 and Ago3 decreased vpiRNA biogenesis without impacting replication of Semliki Forest virus (SFV), Sindbis virus (SINV) and dengue virus [26, 27, 29, 31, 36]. Further experiments suggested that Piwi4 was antiviral against SFV, but not through the piRNA pathway [27].…”
Section: Introductionmentioning
confidence: 99%